How to live longer: lived experience of older adults in Thailand - Kumpeera, Kittisak; Daengthern, Laddawan; Thojampa, Somsak; Udkhammee, Kunchayarat (Jurnal Ners, 2023)
Introduction: Thai population data across the country found that the number of older adults who were aged over 80 years old increased. The researcher was interested in caring of older adults following the context of lifestyle, detail of self care, and social support which make older people live longer than the average life expectancy. The nurses can use obtain information to appropriate health promotion for adults who are becoming older adults. It makes people to good quality of life when they are older and life longevity. Methods: This qualitative research has a purposive sampling method that was used to select ten participants who were aged 80 years and above and from five villages, the inclusion criteria was who can communicate in Thai language and agreed to participate in this research project. An in depth interview using open ended questionnaire were conducted to explore the factors leading to longevity among older people. Results: This study revealed four themes related to longevity in older adults as follows: food type choices, exercise as part of daily life, reduction of stress options, and dealing with illness. Conclusion: The relatives and healthcare providers of older adults should support them to eat healthy food, do regular exercises, volunteer in activities that help society, regularly meditate to calm the mind, and have fast access to health system services. Keywords: food type choices, exercise as part of daily life, reduction of stress options, dealing with illness, Life long